Essai de recherche d’une typologie de la sainte mystique dans l’islam et le christianisme à partir de l’étude de cas de Rabia Adawiyya - Claude-Brigitte Carcenac (Conserveries Mémorielles)
Towards a Typology of Saintly Mysticism in Islam and in Christianity Based on a Case Study : Rabia al-Adawiyya. Despite their emerging in different periods, Christianity and Islam belong to the same geographical sphere and are of common kinship. The two religions are found to share, moreover, a highly unequal attitude towards women even as their respective messages feature a universal and non-discriminatory character. Women acquire, it would seem, a significant standing by virtue of achieving saintliness, often by way of mysticism.Identifying a typology of saintly mysticism specific to women and common to both religions holds out several prospects, including that of outlining a phenomenology, over and above religious creeds, which is specifically feminine in gender. The study focuses on a noteworthy eighth-century figure of Sufism, Rabia al-Adawiyya, and examines her case in four aspects : the hagiographic account of a saint’s life in its three main stages (birth, the taking up of a saintly life, death), the forms that the quest for divine love takes, the manifestations of the divine calling, and finally, the place of mysticism in a man-centered environment.